Pervasive roles of microRNAs in cardiovascular biology - Small, Eric M. (2011)
First recognized as regulators of development in worms and fruitflies, microRNAs are emerging as pivotal modulators of mammalian cardiovascular development and disease. Individual microRNAs modulate the expression of collections of messenger RNA targets that often have related functions, thereby governing complex biological processes. The wide-ranging functions of microRNAs in the cardiovascular system have provided new perspectives on disease mechanisms and have revealed intriguing therapeutic targets, as well as diagnostics, for a variety of cardiovascular disorders.